(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
The objectives of this study include knowing the relationship between students’ involvement in Laboratory Activities (KL) and their success in learning Physics; knowing that KL is one of the excellent learning strategies to improve physics learning concepts; knowing how to use simple or very cheap materials in KL to achieve learning objectives. This research method is a descriptive qualitative method that describes the opinions and answers of participants. The sample of this study was 25 students, who were divided into 5 groups. Each group carried out all the KL that had been prepared. The instruments used to analyze this activity are protocol that guides the KL that has been prepared by the author for each KL; questionnaire: is one of the assessment instruments to collect information and opinions from participants according to the questions that have been prepared relevant to the implementation of KL and allows to include the analysis made by students on the KL developed by themselves. The results of the questionnaire analysis showed that the students had very good skills according to their understanding in preparing and installing the equipment for each KL, regarding the language of instruction (Portuguese) used there were some students who requested that the language of instruction used needed to be adapted to the understanding of the students because it was quite difficult for them to understand. In relation to the implementation of the KL, the students were successful in the implementation of the KL in the Laboratory, material handling, and exploration of the situation (distance, angle, etc.) which contributed very significantly to understanding the terms used and the phenomena studied in this study. While related to understanding, most students are able to use the measurement results well. The conclusions from the results of this study are a) KL has a very relevant role in understanding existing theories and is a motivator for scientific learning; b) the importance of student responsibility to be themselves in preparing and designing experiments, taking measurements, and obtaining values of physical quantities; c) related to the design and preparation of materials and controlling conditions for the implementation of KL